SUITABILITY OF THE CROPPING SYSTEM SOME VARIETIES OF MAIZE (Zea mays L.) AND SOYBEAN (Glycine max L.) WITH INTERCROPPING SYSTEM ON DRY LANDS - Xena Widya Iswara; Ami Suryawati; Nurngaini Nurngaini; Kristamtini Kristamtini (Jurnal Agrivet, 2021)
Intercropping is an attempt from agriculture’s intensification program which purposes to obtain optimum yield and maintain soil’s fertility. This research aims to know whether intercropping systems have better crops and higher yields than monoculture systems. This research was conduct on May-August 2020 at Trengguno Kidul, Sidorejo, Ponjong, Gunung Kidul. The design of the experiment was arranged in a randomized block design (RBD) one factor and three blocks. One factor namely ST 1: soybean monoculture Dega variety, ST2: maize monoculture Dega 1 variety, ST 3: Maize monoculture Srikandi Ungu variety, ST 4: Intercropping system of soybean Dega 1variety with maize Pulut Uti 1 variety, ST 5: Intercropping system of soybean Dega 1 variety and maize Nasa 29 variety, ST 6: Intercropping system of soybean Dega 1 variety with maize Pulut Uri 1 variety, ST 7: Intercropping system of soybean Dega 1 variety and maize Srikandi Ungu variety. Data were analyzed statistically using SAS (Statistical Analysis System) ANOVA 5% and further tested with the Duncan test at a significant level of 5%. The results show soybean on monoculture system has better growth and yield than intercropping while on maize of Pulut Uri and Nasa 29 plant intercropping system has the same growth and yield than monoculture. Combination intercropping of maize variety namely Srikandi Ungu and Soybean variety namely Dega proved better growth and yield.